Pemanfaatan Sistem Informasi Geografis Untuk Kajian Tingkat Kerentanan Banjir di Kecamatan Tirto Kabupaten Pekalongan - Nur, Rokhayati; Sriyono, Sriyono (Geo-Image, 2018)
This study purposed to: (1) Identify flood susceptibility level by using Geographic Information System (2) To know flood characteristics that occur in accordance with flood susceptibility level (3) Formulate effort of area management based on flood susceptibility level. The research use descriptive quantitative research method, with technique scoring and overlay for data analysis technique it. The results showed susceptible flood susceptibility covering an area of 11.07 km², a very susceptible class of 7.98 km² and a slightly susceptible class of 1.89 km². Flood characteristics in the form of deluge and rob (annual) floods occur in very susceptible classes, seasonal floods (5-10 annual repeat periods) occur in flood-prone classes, rather susceptible flooded classes are never flooded areas that result in losses. Efforts to manage potentially flooded areas in the regions are particularly susceptible to the construction of flood controls (dikes / river and marine water walls, polder, flood profing), susceptible and somewhat susceptible areas of management of the area not much different from the normalization of rivers and drainage improvements, making artificial recharge on multilevel buildings and settlement development must be in accordance with the provisions of spatial law and the development of water conservation technology in vacant land.